FASOLA (farming solution application): Integrating IoT innovation in vertical farming to support food security and economic sustainability - Krisatya, Georgia; Setiawan, Nadine Puteri; Fatahhillah, Ilham (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Food security is a crucial aspect in human survival. The increasing population poses a major challenge for Indonesia to meet food demand and achieve self-sufficiency. To support the economy and sustainable agriculture, it is necessary to increase food productivity through a land-efficient system. Renewable technologies are needed to help farmers optimize the use of limited land for efficient, sustainable, and adaptable agricultural activities in various regions, especially in urban areas. Methods: The Fasola application was developed using a prototype design methodology that includes four main stages: user needs analysis, visual design (wireframe and mockup), IoT technology development and integration, and user test-based evaluation and revision. This approach aims to create innovative and user-friendly solutions to support productivity and sustainability of IoT-based vertical farming. Findings: Fasola is an IoT-based application that supports vertical farming in urban areas to improve the efficiency and sustainability of food production. Its features allow farmers to monitor the planting environment, manage irrigation and energy, and market their crops digitally. The application increases productivity, reduces operational cost, and strengthens local food security. With the support of education and community approaches, Fasola contributes to environmentally friendly agriculture and the transition to a green economy. Conclusion: Fasola (Farming Solution Application) is an appropriate technological innovation in the digital era that supports food security and a sustainable economy. Its features help optimize the use of resources, reduce agricultural waste, and increase production efficiency, allowing farmers to manage the entire farming process in one integrated platform. Novelty/Originality of this article: This study introduce an IoT based application innovation that provides practical support for modern agriculture on limited land. This application integrates hydroponic farming and vertical farming through advanced features, offering a sustainable system that can contribute to food security.